2019
DOI: 10.1104/pp.19.00266
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Roles of Secretory SNARE SYP132 in Plasma Membrane H+-ATPase Traffic and Vegetative Plant Growth

Abstract: The plasma membrane proton (H +)-ATPases of plants generate steep electrochemical gradients and activate osmotic solute uptake. H +-ATPase-mediated proton pumping orchestrates cellular homeostasis and is a prerequisite for plastic cell expansion and plant growth. All evidence suggests that the population of H +-ATPase proteins at the plasma membrane reflects a balance of their roles in exocytosis, endocytosis, and recycling. Auxin governs both traffic and activation of the plasma membrane H +-ATPase proteins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(91 citation statements)
references
References 103 publications
(208 reference statements)
4
79
0
Order By: Relevance
“…Yet, the two Qa-SNARE null mutants show very different phenotypes in pathogen defense and abiotic stress resistance (Collins et al, 2003;Zhang et al, 2007;Eisenach et al, 2012) and the Qa-SNAREs mediate the traffic of different subsets of secretory cargo (Rehman et al, 2008;Waghmare et al, 2018). These, and associated studies (Reichardt et al, 2011;Hashimoto-Sugimoto et al, 2013;Xia et al, 2019;Zhang et al, 2019), implicate a functional network of trafficking and related regulatory protein partners that is substantially more dynamic than may be deduced from an analysis of gene families.…”
Section: Exo70 and Snare Redundanciesmentioning
confidence: 99%
“…Yet, the two Qa-SNARE null mutants show very different phenotypes in pathogen defense and abiotic stress resistance (Collins et al, 2003;Zhang et al, 2007;Eisenach et al, 2012) and the Qa-SNAREs mediate the traffic of different subsets of secretory cargo (Rehman et al, 2008;Waghmare et al, 2018). These, and associated studies (Reichardt et al, 2011;Hashimoto-Sugimoto et al, 2013;Xia et al, 2019;Zhang et al, 2019), implicate a functional network of trafficking and related regulatory protein partners that is substantially more dynamic than may be deduced from an analysis of gene families.…”
Section: Exo70 and Snare Redundanciesmentioning
confidence: 99%
“…Together, the results presented by Xia et al (2019) clearly show that the Qa-SNARE SYP132 plays a role in intracellular trafficking of H + -ATPases and contributes to the regulation of auxin-mediated acid growth. The effects of SYP132 on H + -ATPase trafficking are somewhat counterintuitive, since SYP132 is a target SNARE localized to the PM.…”
Section: The Snare Syp132 Fine-tunes Proton Transporter Levels At Thementioning
confidence: 59%
“…SYP121 and SYP122 mediate the majority of PM trafficking and have some overlapping and distinct functions (Karnik et al, 2017). In this issue of Plant Physiology, Xia et al (2019) identify a role for the Qa-SNARE SYP132 in trafficking of H + -ATPases to the PM to facilitate acid growth.…”
Section: The Snare Syp132 Fine-tunes Proton Transporter Levels At Thementioning
confidence: 98%
“…This supports a sofar understudied role for PM-SNARE complex formation in the regulation of endocytic traffic in plants. Interestingly, it has recently been shown that AtSYP132 (the ortholog of MtSYP131) affects the endocytic traffic of an H+-ATPase, with which it interacts (Xia et al, 2019). Induced expression of AtSYP132 reduced the amount of H+-ATPase proteins at the PM thereby affecting the acidification of the cell wall.…”
Section: Discussionmentioning
confidence: 99%